CONCEPTUALIZATION OF THE DIAGNOSTICS MODEL OF FUTURE TEACHER'S CULTURE CREATIVITY GROWTH IN CONDITIONS OF MULTICULTURAL EDUCATION - Kateryna Averina (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The paper identifies the main goal of multicultural education which is not determined by the number of knowledge and skills, but by personal development in the context of culture that means considering one's own worldview, characterized by originality and always by personal and variable worldview, creating the conditions for the development and self-realization of each person which adheres to human values and also formation of the skills to learn for life. In the course of the study it was found out that activation of the process for culture creativity growth will be taking place under the conditions providing actualization of capabilities and resources of multicultural education and its impact on a future teacher's identity formation. The diagnostics model based on conceptual understanding of the process of cultural and creative growth of personality and grasp of multiculturedness as a personal ability of man to have a desire and capability to live in the multicultural environment.